Biomechanical effects of manipulating peak vertical ground reaction force throughout gait in individuals 6–12 months after anterior cruciate ligament reconstruction. (June 2020) - Evans-Pickett, Alyssa; Davis-Wilson, Hope C.; Luc-Harkey, Brittney A.; Blackburn, J. Troy; Franz, Jason R.; Padua, Darin A.; Seeley, Matthew K.; Pietrosimone, Brian
Abstract: Background: We aimed to determine the effect of cueing an increase or decrease in the vertical ground reaction force impact peak (peak in the first 50% of stance) on vertical ground reaction force, knee flexion angle, internal knee extension moment, and internal knee abduction moment waveforms throughout stance in individuals 6–12 months after an anterior cruciate ligament reconstruction. Methods: Twelve individuals completed 3 conditions (High, Low, and Control) where High and Low Conditions cue a 5% body weight increase or decrease, respectively, in the vertical ground reaction force impact peak compared to usual walking. Biomechanics during High and Low Conditions were compared to the Control Condition throughout stance. Findings: The High Condition resulted in: (a) increased vertical ground reaction forces at each peak and decreased during mid-stance, (b) greater knee excursion (i.e., greater knee flexion angle in early stance and a more extended knee in late stance), (c) greater internal extension moment for the majority of stance, and (d) lesser second internal knee abduction moment peak. The Low Condition resulted in: (a) vertical ground reaction forces decreased during early stance and increased during mid-stance, (b) decreased knee excursion, (c) increased internal extension moment throughout stance, and (d) decreased internal knee abduction moment peaks. Interpretation: Cueing a 5% body weight increase in vertical ground reaction force impact peak resulted in a more dynamic vertical ground reaction force loading pattern, increased knee excursion, and a greater internal extension moment during stance which may be useful in restoring gait patterns following anterior cruciate ligament reconstruction. Highlights: Vertical ground reaction force impact peak can be modified with real-time feedback. A single cue can be used to modify multiple gait biomechanics throughout stance. Cueing a higher impact peak leads to greater knee flexion excursion during stance. Cueing a higher impact peak leads to increased internal knee extension moment. Cueing a lower impact peak leads to a stiffened knee gait strategy.